Geological setting and evolution of the Omitiomire Cu deposit in the Southern Zone accretionary prism of the Damara Belt, Namibia - Kitt, Shawn (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.